MILLENNIAL WILLINGNESS TO WEAR A FACE MASK (WTW) AFTER THE COVID-19 VACCINATION - Mui Ling Dyana, Chang; Yin Ling Tam, Adeline; Thara Zainal; Kelvin Yong, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The COVID-19 pandemic has had a profound effect on communities worldwide, with governments imposing restrictions on movement, global vaccination, quarantine, social distance measures, stay-at-home policies, and other preventative measures such as mandatory use of face masks. Despite widespread agreement that symptomatic individuals and those working in healthcare settings should continue to use the face mask following COVID-19 vaccination, discrepancies were observed in the public and societies raising awareness among Malaysian millennials. Global efforts to develop a vaccine have been accelerated to alleviate the growing burden of COVID-19. Thus, vaccination significantly decreased adverse outcomes such as non-ICU hospitalisation, as well as ICU hospitalisation and death, in several countries. Similarly, during the COVID-19 pandemic, the use of face masks by the Malaysian population, particularly the millennial generation, became widespread. However, few studies have been conducted on the millennials' willingness to continue using face masks following their COVID-19 vaccination programme in Malaysia. The purpose of this study is to gain insight into the factors that influence millennials' willingness to wear face masks following their COVID-19 vaccination programme in Malaysia. The application of the Theory of Planned Behaviour (TPB) as the guiding principle relationship enables an understanding of the millennials' continued intention to use a face mask following the COVID-19 vaccination. The hypotheses were tested using a partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. The study's significance is that it advances the theoretical methodology and has practical implications for the public, scholars and practitioners, marketers, healthcare, and government in terms of prioritising willingness to continue using face masks following COVID-19 vaccination among Malaysian millennials.